SIMPLE STORIES EXTENSIVE READING METHOD: EFLSTUDENTS’ READING COMPREHENSION IMPROVMENT - Wamah Yaya Saparang; Aminah Suriaman; Maf’ulah; Nadrun (Universitas Muhammadiyah Makassar, 2026)
Reading comprehension is the ability to capture and understand the meaning of text. However, many students have difficulty in understanding and remembering the information they read. The objective of this research is to find out the effectiveness of the Simple Stories Extensive Reading method in improving students' reading comprehension at SMP Negeri 2 Lore Tengah. This research used a pre-experimental research design. The sample was selected through random sampling. The researchers used a pretest and posttest to collect the data. The results showed that the mean score on the pretest was 29.95, which significantly increased to 80.67 on the posttest. In addition, the significance value (2 tailed) (p = 0.001) was lower than the alpha level (0.05), which indicated that the alternative hypothesis was accepted. This research implies that the Simple Stories Extensive Reading method can increase students interest in reading, make students less likely to get bored, and create a more enjoyable learning process.